The Structure and Content of MARC 21 Records in the Unicode Environment - Aliprand, Joan M. (Information Technology and Libraries, 2005)
MARC 21 records may be encoded in individual character sets (including ASCII and ANSEL) or in Unicode (as UTF-8). This paper considers the effect of the use of Unicode without any constraints on the structure and data content of MARC 21 records. The case of Model A records where Latin is the preferred script is examined in particular detail.